Comparative and Legal Analysis of Criminal and Legal Protection of Individual Components of Natural Environment: European Experience - SAVCHENKO, Andrii; BABIKOV, Oleksandr; OLIINYK, Olena (Journal of Advanced Research in Law and Economics; Vol 8 No 7 (2017): JARLE Volume VIII Issue 7(29) Winter 2017, 2017)
The article is dedicated to criminal and legal protection of both the natural environment, and its individual components. This research describes legislation on environmental protection in the most developed European countries such as Spain, Italy, Poland, Germany, and also pays attention to international experience. There are laws on criminal responsibility for attacks on objects of natural environment and international acts have been analysed.